Extralobar Pulmonary Sequestration in the Right Lower Thoracic Region Associated with Esophageal Fistula - Feng, Xing; Xiong, Xiao-Ling (The Thoracic and Cardiovascular Surgeon, 2013)
Extralobar pulmonary sequestrations (ELS) are most commonly found within the left thoracic cavity. We report the case of a 10-year-old girl with ELS in the right thoracic cavity, associated with esophageal fistula. Chest computed tomography scans revealed a parenchymal mass between the right lower lobe and the diaphragm. At last, successful resection of the mass and repair of the esophageal fistula were performed. The girl recovered uneventfully.
Keywords: extralobar pulmonary sequestration; esophageal fistula